Contribution of Neuroinflammation to the Pathogenesis of Cancer Cachexia - Alessio Molfino; Gianfranco Gioia; Filippo Rossi Fanelli; Alessandro Laviano (Hindawi Limited, 2015)
Inflammation characterizes the course of acute and chronic diseases and is largely responsible for the metabolic and behavioral changes occurring during the clinical journey of patients. Robust data indicate that, during cancer, functional modifications within brain areas regulating energy homeostasis contribute to the onset of anorexia, reduced food intake, and increased catabolism of muscle mass and adipose tissue. In particular, functional changes are associated with increased hypothalamic concentration of proinflammatory cytokines, which suggests that neuroinflammation may represent the adaptive response of the brain to peripheral challenges, including tumor growth. Within this conceptual framework, the vagus nerve appears to be involved in conveying alert signals to the hypothalamus, whereas hypothalamic serotonin appears to contribute to triggering catabolic signals.